1994
DOI: 10.1063/1.111701
|View full text |Cite
|
Sign up to set email alerts
|

Effects of NH3 nitridation on oxides grown in pure N2O ambient

Abstract: Effects of NH3 nitridation on the chemical and electrical properties of N2O oxides have been studied. Compared with NH3-nitrided SiO2, NH3 nitridation does not degrade the electrical properties of N2O oxides, thus resulting in superior impurity diffusion barrier properties, while preserving excellent interface immunity to hot-carrier injection and much lower charge trapping. Correlation studies between the chemical and electrical properties of NH3-nitrided N2O and NH3-nitrided SiO2 have been done to explain th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(40 citation statements)
references
References 11 publications
2
38
0
Order By: Relevance
“…But, the energy difference between Si 2 ANAO and the above-mentioned peak is very small and therefore, their individual contribution to the main N 1s peak cannot be ascertained. Also, a peak present around 398.65 eV due to SiAN@H 2 type of bonding is reported by Bhat et al [23]. The energy difference between the two peaks SiAN@H 2 and NA(SiO) x is quite small to be distinguished; as a result, the exact assignment of the second peak is still not well established.…”
Section: Resultsmentioning
confidence: 91%
“…But, the energy difference between Si 2 ANAO and the above-mentioned peak is very small and therefore, their individual contribution to the main N 1s peak cannot be ascertained. Also, a peak present around 398.65 eV due to SiAN@H 2 type of bonding is reported by Bhat et al [23]. The energy difference between the two peaks SiAN@H 2 and NA(SiO) x is quite small to be distinguished; as a result, the exact assignment of the second peak is still not well established.…”
Section: Resultsmentioning
confidence: 91%
“…Oxynitride prepared by NH 3 nitridation would introduce a large amount of traps because of the hydrogen incorporation and the amount of nitrogen incorporation at high temperature (>1000°C) is still too low (<5%) [70,71,[85][86][87] to improve the j value. With the advantages of low hydrogen content and the selflimited low growth rate, N 2 O oxide permits a better control of film thickness and slightly increases the resistance to boron diffusion [88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105].…”
Section: The Prospect and Process Variantsmentioning
confidence: 99%
“…3a depicts the nitrogen 1s XPS spectra of the asdeposited oxynitride films and films with annealing at different temperatures for 3 h. It can be seen that the N 1s for non-annealed sample has a peak at the energy of 398.6 eV. It indicates that the nitrogen atoms in the oxynitride are essentially in the form of Si-N bonding with high hydrogen content [15]. Si-N bond in stoichiometric Si 3 N 4 film has a feature peak at around 397.4 eV.…”
Section: Resultsmentioning
confidence: 94%
“…The excess silicon and hydrogen will result in the shift of the N 1s to higher energy side. In NH 3 nitrided oxide, Bhat et al [15] found that the N 1s peak is 398.6 eV which is attributed to the SiAN@H 2 . For samples with 3 h annealing at temperatures larger than 800°C, the intensity of the N 1s peak reduced pronounced and its location shifts to even higher energy side to about 399 eV.…”
Section: Resultsmentioning
confidence: 97%